Assessment of Muscle Fatigue Associated with Prolonged Standing in the Workplace - Isa Halim; Abdul Rahman Omar; Alias Mohd Saman; Ibrahim Othman (2012)
The objectives of this study were to determine the psychological fatigue and analyze muscle activity of production workers who are performing processes jobs while standing for prolonged time periods.The psychological fatigue experienced by the workers was obtained through questionnaire surveys. Meanwhile, muscle activity has been analyzed using surface electromyography (sEMG) measurement. Lower extremities muscles include: erector spinae, tibialis anterior, and gastrocnemius were concurrently measured for more than five hours of standing. Twenty male production workers in a metal stamping company participated as subjects in this study. The subjects were required to undergo questionnaire surveys and sEMG measurement.Results of the questionnaire surveys found that all subjects experienced psychological fatigue due to prolonged standing jobs. Similarly, muscle fatigue has been identified through sEMG measurement. Based on the non-parametric statistical test using the Spearman's rank order correlation, the left erector spinae obtained a moderate positive correlation and statistically significant (r(s) = 0.552, p < 0.05) between the results of questionnaire surveys and sEMG measurement.Based on this study, the authors concluded that prolonged standing was contributed to psychological fatigue and to muscle fatigue among the production workers.